Electronic Business and Marketing New Trends on its Process and Applications - Matsuo, Tokuro; Colomo-Palacios, Ricardo (Studies in Computational Intelligence, 2013)
Electronic business today is not only business transactions supported in information and communication technologies; it is a new way of communicating and integrating with customers, suppliers, employees and other stakeholders. In this scenario, electronic business is now part of a wider economic context that is causing radical transformations in business and organizations including the entire value chain from customer service to supply chain management. One of the areas affected is marketing. Given that the new technologies have enabled firms to reach out to global customers and has provided them with the opportunity to customize their strategies and offerings in an unprecedented way, the dynamics of marketing must be surveyed in order to study the impact of new trends like mobile customer relationship management or mass customization on marketing function. This book provides an overview of the e-Business and Marketing areas by uniting various papers from these fields. "Electronic Business and Marketing" includes theory and practice on electronic business and marketing from an academic and professional viewpoint providing also a forum for the exchange of research ideas and industry practices in these knowledge areas among practitioners, researchers and students.  .